U.S. Fiscal Policies and Priorities for Long-Run Sustainability - Muhleisen, Martin (Occasional Papers; Occasional Paper ;, 2004)
This paper presents an overview of recent U.S. fiscal developments and discusses possible implications of the sharp turn around in the government's fiscal position. Against this back ground, it also reviews key policy challenges that will need to be addressed to cope with the mounting pressures on public retirement and health care systems during the next decade. The study draws principally from back ground papers that were prepared for the IMF staff's annual consultation discussions with the U.S.authorities in 2002 and 2003.